SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF TEACHING BASIC TECHNICAL ACTIONS IN FOOTBALL - Abduqodirov Davronbek Solijon o‘g‘li (Bright Mind Publishing, 2026)
This scientific and methodological article provides a systematic analysis of the theoretical and practical foundations of teaching the basic technical actions in football (ball receiving and passing, dribbling, feints, shooting, ball control, heading, and defensive technical elements). Special attention is given to the priority principles of systematization, step-by-step progression, individualization, variable practice, and the approximation of exercises to real game conditions in the development of technical preparedness. The principles of motor learning theory (stages of skill acquisition, variable practice, contextual interference, and types of feedback) are adapted to the football technique teaching process. In addition, a four-stage teaching model (demonstration–simplification–complication–game integration), an algorithm for diagnosing and correcting typical technical errors, training session structure, planning of technical load within a microcycle, and control criteria are proposed. The presented approach contributes to improving technical consistency, accelerating decision-making in game situations, and reducing technical errors during competitive activity among young football players.
Keywords: Football; technical preparedness; methodology of teaching technique; step-by-step progression; individualization; variable practice; feedback; technical errors; control criteria; small-sided games.